Die Rückforderung von Glücksspieleinsätzen im Internet: Überlegungen zu den so genannten "Spielerklagen" - Dutta, Anatol; Heinze, Christian (Spiel und Recht, 2023)
An ever-growing number of gamblers who chanced their luck online before German gaming law was further liberalised in 2021 have been bringing their cases to German civil courts and attempting to reclaim stakes paid to internet gambling companies. These so-called »Spielerklagen« have so far met with varying degrees of success and raise numerous issues that have not yet been comprehensively discussed.